Integrated Multiregional Analysis Proposing a New Model of Colorectal Cancer Evolution. - Ryutaro Uchi; Yusuke Takahashi; Atsushi Niida; Teppei Shimamura; Hidenari Hirata; Keishi Sugimachi; Genta Sawada; Takeshi Iwaya; Junji Kurashige; Yoshiaki Shinden; Tomohiro Iguchi; Hidetoshi Eguchi; et al. (PLoS Genetics, 2016)
Understanding intratumor heterogeneity is clinically important because it could cause therapeutic failure by fostering evolutionary adaptation. To this end, we profiled the genome and epigenome in multiple regions within each of nine colorectal tumors. Extensive intertumor heterogeneity is observed, from which we inferred the evolutionary history of the tumors. First, clonally shared alterations appeared, in which C>T transitions at CpG site and CpG island hypermethylation were relatively enriched. Correlation between mutation counts and patients' ages suggests that the early-acquired alterations resulted from aging. In the late phase, a parental clone was branched into numerous subclones. Known driver alterations were observed frequently in the early-acquired alterations, but rarely in the late-acquired alterations. Consistently, our computational simulation of the branching evolution suggests that extensive intratumor heterogeneity could be generated by neutral evolution. Collectively, we propose a new model of colorectal cancer evolution, which is useful for understanding and confronting this heterogeneous disease.